Peran Guru IPS Dalam Menanamkan Sikap Spiritual dan Sosial Pada Peserta Didik di SMP Negeri 1 Gempol Kabupaten Cirebon - Almas Anieq; Mahdi, Mahdi; Apriyanda Kusuma Wijaya (FKIP, Universitas Palangka Raya, 2023)
Spiritual and social attitudes have often been instilled by teachers, but are still not fully embedded in students. The aims of this study were 1) to describe the role of social studies teachers in applying spiritual attitudes to students, 2) to describe the application of social attitudes to students carried out by social studies teachers. 3) Knowing the obstacles in instilling spiritual and social attitudes in students. This study uses qualitative methods with a phenomenological approach. Data collection tecniques used are observation, interviews and documentation by testing the validity of the data using triangulation. The role of the teacher in education makes the teacher a hero who participates in the implementation of education. Spiritual attitude reflects religious character. Spirituality is a character value related to humans and their God. Social attitude is a very important affective concept in education.The results of the study show that changes in students' spiritual and social attitudes lead to positive things. The role of social studies teachers and working with various parties such as parents, the environment around the house and school in instilling students' spiritual and social attitudes has a significant role